Crystal Structures of d-Lyxono-1,4-lactone and Its O-Tosyl Derivative - Anna Sosnowska; Jarosław Chojnacki; Justyna Samaszko-Fiertek; Janusz Madaj; Barbara Dmochowska (Molecules)
γ- and δ-lactones were formed by bromine oxidation of commercially available D-lyxose, as confirmed by IR analysis. The former was isolated, and its structure was confirmed by NMR spectra and X-ray analysis. In this structure, the presence of both intermolecular and intramolecular hydrogen bonds was found. Intermolecular interactions in the crystal were illustrated using the Hirshfeld surfaces. Due to steric reasons, 3,5-O-isopropylidene-d-lyxono-1,4-lactone was formed, which in a further step led to the formation of a 2-O-tosyl derivative. Its structure was confirmed by X-ray diffraction analysis. The additional ring of the O-isopropylidene derivative caused the lactone ring to change conformation to 3E. In the crystal structure of this compound, only C-H⸱⸱⸱O intermolecular interactions were present, as confirmed by the Hirshfeld surface analysis.